EFFECT OF SOCIALIZATION AND TRAINING ON UNDERSTANDING STRESS MANAGEMENT (CASE STUDY OF SMKS PARULIAN I MEDAN) - Anda Yanny; Ronda Deli Sianturi (Enrichment : Journal of Management, 2022)
The Online Learning System during the Covid-19 Pandemic is considered to be less effective students, because this system is not directly face to face with teachers, it makes students and students of SMKS Parulian I Medan less understanding of the learning materials provided by teachers, especially if their internet card network is disrupted, or who have not bought internet packages because they have not been given money by their parents. Their incomprehension of the material provided makes them lazy to do the tasks and exercises given by the teacher. When the deadline is collection tasks or exercises, they will start busy working on the threes and eventually they stress themselves. Severe stress can result in physical attacks on the body such as lazy or forgetting to eat, the brain is used to think about finding answers to tasks given by teachers. Then this will be bad for their physical health and fitness. It is even feared that these teenagers will be grazed into negative things. Then the author is interested in making research. The aim is to see if socialization and training affect students' understanding of stress management.